Alalakh and its neighbours: proceedings of the 15th Anniversary Symposium at the New Hatay Archaeology Museum, 10-12 June 2015 - Yener, K. Aslıhan; Ingman, Tara (Ancient Near Eastern studies / Supplement, 2020)
"This volume, Alalakh and its Neighbours, represents the results of the symposium held in honour of the fifteenth anniversary of renewed excavations at Tell Atchana (Alalakh). It brings together results of ongoing interdisciplinary research projects conducted by the large and diverse Tell Atchana team with reflections on Alalakh's connections to its wider social and geographical setting as discussed in the contributions of scholars working at nearby sites in Anatolia, Syria, and the Aegean. The papers here look both inward towards resolving lingering questions from Sir Leonard Woolley's original excavations at the site, as well as new questions that have come up in the renewed excavations concerning life at Alalakh, and outward toward the city's place in a regional context. Covering chronological issues, textual evidence, scientific analyses, and a wide range of material culture (including especially ceramics, metals, stone, and glass), this volume encompasses the recent results of work at this important second millennium BC site"--